Integrating Muslim Immigrant Minorities: The Effects of Narrative and Statistical Messages. (June 2017) - Wojcieszak, Magdalena; Azrout, Rachid; Boomgaarden, Hajo; Alencar, Amanda Paz; Sheets, Penelope
We build on studies on integration and message effectiveness to test whether narrative versus statistical evidence is more effective in promoting openness to Western European norms among different subgroups of Muslim immigrants. We draw on an experiment in which Muslim immigrants living in the Netherlands ( N = 454) saw narrative or statistical messages about gender equality, sexual minority rights, and secularism in public life. We find that the Dutch-born were more receptive to a narrative, while statistical messages generated greater openness to the tested norms among those born in Muslim countries. We interpret these findings in light of different cultural orientations. The study offers a first step toward a framework for understanding evidence effectiveness in multiethnic societies.